Role of intermediaries in shaping climate finance in developing countries - lessons from the Green Climate Fund - Abrar Chaudhury (MDPI, 2020)
Social scientists are increasingly interested in the processes that give shape to global policy solutions. I investigate the issues of intermediation and the role of intermediaries in climate finance. I use the case of the Green Climate Fund (GCF), a new consortium for dedicated funding set up under the United Nations Framework Convention on Climate Change (UNFCCC) to assist developing countries in responding to climate threats, to ask a fundamental question: What role do intermediaries (GCF-accredited and related entities) play in catalysing climate action through climate finance in these countries? This paper offers three propositions focused on the role of intermediaries in the GCF, and tests these using data from the GCF and the wider literature. The results show a growing dominance of international intermediaries in GCF project development and implementation, the low capacity of national intermediaries to conceive and scale projects, and the mismatch between planned and actual funding allocations. Collectively, these outcomes derail the GCF from its core objectives of promoting country ownership of projects, building capacity of local intermediaries, and equitable allocation of funding between mitigation and adaptation. I offer three learning models to help the GCF and intermediaries capitalise on the early lessons from GCF activities and to scale climate finance effectively in developing countries.